Konsep Perencanaan Dakwah Perpustakaan Umum Islam Iman Jama - Rusmala Santi; Muslimin Muslimin (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2016)
Abstract: The presence of Islam Iman Jama Public libraries as a means of providing information in the field of information in the field of Islamic religious sciences have attractive terms to be used as study materials, especially in the perspective of Islam. Therefore, this article has several main goals. First, to express and explain the planning propaganda Public Library Islam Iman Jama Jakarta. Second, to articulate and explain the efforts of the Public Library of Islam Iman Jama in providing various means and information about the study keisslam. Third, explain and put forth the effort Public Library Islam Iman Jama increasing the reading interest of Muslims and efforts to develop the message of Islam.